2017
DOI: 10.4049/jimmunol.1601954
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIIIa Signaling Modulates Endosomal TLR Responses in Human CD4+ T Cells

Abstract: Summary Recognition of antibody-opsonized pathogens by immune cells triggers both toll-like receptor (TLR) and Fc-receptor (FcR) signaling. FcRs endocytose modified nucleic acids bound to antibodies and deliver them to endosomes, where they are recognized by nucleic acid-sensing TLRs (NA-TLRs). We show that in CD4+ T-cells NA-TLRs, TLR3, TLR8 and TLR9 are upregulated by FcγRIIIa-pSyk cosignaling and localize with FcγRIIIa on the cell surface. TLR9 accumulates on the cell surface, where it recognizes CpG oligon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…In human B cells, cosynergistic signaling from ITAM and MyD88 enahnces B cell receptor activation [29]. We previously reported that the TLR9 and FcgRIIIa joint cosignaling enhances IL-17A and IL-21 production [18]. Thus, we analyzed IL-17A and IL-21 prodution from synergistic cosignaling in Bcl6 + T FH cells.…”
Section: In Vitro Fcgriiia Engagement By Ics Induces T Fh Like Cellsmentioning
confidence: 96%
See 4 more Smart Citations
“…In human B cells, cosynergistic signaling from ITAM and MyD88 enahnces B cell receptor activation [29]. We previously reported that the TLR9 and FcgRIIIa joint cosignaling enhances IL-17A and IL-21 production [18]. Thus, we analyzed IL-17A and IL-21 prodution from synergistic cosignaling in Bcl6 + T FH cells.…”
Section: In Vitro Fcgriiia Engagement By Ics Induces T Fh Like Cellsmentioning
confidence: 96%
“…The ICs conjugates were in the range of 23 to 30 µM fluorochrome to-protein ratio. Purification and conjugation was performed as described previously [16,18]. All conjugates were titrated and flow compensation was done using isotype controls.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
See 3 more Smart Citations